River Drying Causes Local Losses and Regional Gains in Aquatic Invertebrate Metacommunity Diversity: A Cross‐Continental Comparison - Daniel Escobar‐Camacho; Julie Crabot; Rachel Stubbington; Judy England; Romain Sarremejane; Núria Bonada; José María Fernández‐Calero; Miguel Cañedo‐Argüelles; Carla Ferreira Rezende; Pierre Chanut; Zoltán Csabai; Andrea C. Encalada; et al. (Global Change Biology, 2025)
Drying river networks include non‐perennial reaches that cease to flow or dry, and drying is becoming more prevalent with ongoing climate change. Biodiversity responses to drying have been explored mostly at local scales in a few regions, such as Europe and North America, limiting our ability to predict future global scenarios of freshwater biodiversity. Locally, drying acts as a strong environmental filter that selects for species with adaptations promoting resistance or resilience to desiccation, thus reducing aquatic α‐diversity. At the river network scale, drying generates complex mosaics of dry and wet habitats, shaping metacommunities driven by both environmental and dispersal processes. By repeatedly resetting community succession, drying can enhance β‐diversity in space and time. To investigate the transferability of these concepts across continents, we compiled and analyzed a unique dataset of 43 aquatic invertebrate metacommunities from drying river networks in Europe and South America. In Europe, α‐diversity was consistently lower in non‐perennial than perennial reaches, whereas this pattern was not evident in South America. Concomitantly, β‐diversity was higher in non‐perennial reaches than in perennial ones in Europe but not in South America. In general, β‐diversity was predominantly driven by turnover rather than nestedness. Dispersal was the main driver of metacommunity dynamics, challenging prevailing views in river science that environmental filtering is the primary process shaping aquatic metacommunities. Lastly, α‐diversity decreased as drying duration increased, but this was not consistent across Europe. Overall, drying had continent‐specific effects, suggesting limited transferability of knowledge accumulated from North America and Europe to other biogeographic regions. As climate change intensifies, river drying is increasing, and our results underscore the importance of studying its effects across different regions. The importance of dispersal also suggests that management efforts should seek to enhance connectivity between reaches to effectively monitor, restore and conserve freshwater biodiversity.